Metal ceramic shielding material for shielding neutrons and gamma rays and preparation method thereof
By using (WxMo1-x)AlB-MAB phase cermet material, using its unique ternary layered nanostructure and metal cermet dual characteristics, the problem of poor comprehensive shielding performance of existing neutron and gamma ray shielding materials in a variety of energy ray mixing fields is solved, and efficient shielding of neutron and gamma rays is achieved, and excellent mechanical and thermal properties are achieved.
Patent Information
- Application Number
- CN202411390481.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-08
AI Technical Summary
The existing neutron and gamma-ray shielding materials have poor integrated shielding performance in the mixed fields of multiple energy rays, and have insufficient mechanical properties and corrosion performance in high temperature and extreme environments.
The (WxMo1-x)AlB-MAB phase cermet shielding material is used, which consists of elements such as tungsten, molybdenum, boron and aluminum. It is prepared by vacuum hot pressing to form a high-purity ternary layered nanostructure, which has the dual characteristics of metal and ceramic.
This material has excellent shielding characteristics for neutrons and gamma rays in various energy segments, and has good mechanical properties, electrical conductivity, thermal conductivity, thermal stability and high-temperature oxidation resistance. It is suitable for small and mobile reactors and other occasions.
Smart Images

Figure CN119506680A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of neutron shielding materials, and in particular relates to a metal ceramic shielding material and a preparation method thereof. Background Art
[0002] In view of the different forms of radiation generation and the application characteristics of nuclear technology, traditional neutron shielding materials are difficult to meet the requirements. In many special small nuclear reactors (such as compact small fusion reactors, mobile small fission reactors) and nuclear facility application sites, there are usually mixed fields of multiple energy rays. The radiation shielding materials must not only have extremely high comprehensive shielding effectiveness for multiple rays, but also have certain structural mechanical properties, withstand extreme environmental assessments, and have extremely high performance functional / structural integrated neutron / gamma ray shielding materials, so as to greatly simplify the shielding structure and realize the miniaturization of the shielding structure.
[0003] Among the typical metal-based functional structure integrated radiation shielding materials, only boron steel is relatively mature in application. It has good thermal neutron absorption performance, γ-ray shielding performance and excellent mechanical properties. Due to the limited amount of boron added to boron steel, if the ideal neutron absorption effect is to be achieved, the neutron absorption capacity must be improved by increasing the thickness of boron steel; aluminum-based boron carbide composite materials are the most widely studied and applied neutron absorption materials because they can add a higher content of boron and inherit the good mechanical properties and thermal conductivity of aluminum. However, it has almost no shielding ability for γ-rays and its low operating temperature also limits some of its applications, such as fusion reactor shielding blanket materials. In recent studies, WB / Al composite materials made by adding tungsten and boron elements to aluminum matrix (201310176166.4, 201811591037.0)) were prepared. Due to the limited amount of boron and W added, the composite materials formed had unsatisfactory comprehensive shielding performance for fast neutrons and γ-rays, high-temperature mechanical properties and corrosion properties. The MH-B-Al (MH: metal hydride) shielding material (201711336252.1, 202210992472.4), which is a composite of aluminum with titanium hydride, zirconium hydride and boron, has good fast neutron moderation and absorption properties, but generally hydrides begin to decompose at 300-500°C, and the decomposition will be accelerated in an irradiation environment.
[0004] In view of the application defects of the above-mentioned materials, the present invention has efficient shielding characteristics for neutrons and gamma rays in various energy bands, and provides a high-density, high-temperature functional / structural integrated neutron and gamma-ray comprehensive shielding material, which is expected to be used in various reactors and various energy ray mixed field facilities, so as to greatly simplify the shielding structure and realize the miniaturization of the shielding structure. Summary of the invention
[0005] The object of the present invention is to provide a metal ceramic shielding material with a simple structure and high-efficiency shielding properties for neutrons and gamma rays in various energy bands, and a preparation method thereof.
[0006] The metal ceramic shielding material for shielding neutrons and gamma rays provided by the present invention is (W x Mo 1-x )AlB-MAB phase metal ceramic shielding material is a 222 type MAB solid solution phase compound (in bulk) with ternary layered nanostructures. It is a monoclinic cubic crystal structure with a space group of Cmcm. Its unit cell is composed of alternating stacking of MB units and A atomic planes. The compound is composed of elements W, Mo, Al (or 6061Al alloy) and B. Mo is the solid solution atom of W at the M position. In the atomic concentration of Mo, x is 5-40at%. The alloying elements Si, Mg and other atoms in the 6061Al alloy are mainly at the A position. (6061Al alloy is the product model of Al alloy and is well known to the standard).
[0007] This compound phase metal ceramic shielding material has extremely high concentrations of W and B, and has excellent shielding properties for neutrons and gamma rays in various energy ranges; on the other hand, this unique structure gives the material dual properties of metal and ceramic, that is, good mechanical properties, excellent electrical and thermal conductivity, high thermal stability and high-temperature oxidation resistance. The addition of solid solution atomic Mo is mainly to increase the decomposition temperature of the compound phase; replacing Al with 6061Al alloy to form a multi-element solid solution at the A position can improve the mechanical properties of the MAB phase.
[0008] There are few reports on the preparation of WAlB-MAB bulk materials. Peter once tried to prepare WAlB by hot pressing, but due to process technology problems, only low W content (Mo) containing many impurities was synthesized. x W 1-x )AlB (x>0.75, purity not higher than 74.3±0.8mol.%.) solid solution, and failed to successfully synthesize WAlB and high W content (W x Mo 1-x )AlB (x>0.25) solid solution. The present invention uses tungsten powder, molybdenum powder, boron powder and aluminum powder (or 6061Al alloy powder) in a ratio of (0.6-0.95): (0.05-0.4): (0.8-1.2): (1.0-2.0) and vacuum hot pressing to successfully prepare (W) with a phase purity of more than 92-96wt.%. x Mo 1-x )-MAB phase materials.
[0009] The present invention provides (W x Mo 1-x) A method for preparing an AlB-MAB phase metal ceramic shielding material, the specific steps being:
[0010] Step 1, using boron powder, tungsten powder, molybdenum powder and aluminum powder (or 6061Al alloy powder) as raw materials to prepare raw materials, and zinc stearate can be added as an active agent to reduce the situation of powder sticking to the wall and the ball during the ball milling process, improve the powder yield, and prevent cold welding;
[0011] Step 2, adding ball milling media to the original ingredients, and dry-milling and mixing at a predetermined speed for a predetermined time on a ball mill to obtain a mixed material;
[0012] Step 3, separating the mixed material and the ball milling medium with a sieve to obtain a mixed material;
[0013] Step 4, pre-pressing the dried mixed material, and then heating and pressurizing the mixed material in a vacuum environment or a protective atmosphere at a predetermined heating rate and a predetermined pressurizing rate, and after reaching a predetermined sintering temperature and a predetermined pressure, sintering the mixed material at a predetermined heat preservation and pressure preservation time to obtain a sintered block;
[0014] Step 5: Cool the sintered block to room temperature at a predetermined cooling rate to obtain a high-purity and dense (W x Mo 1-x )AlB-MAB phase ceramic bulk material.
[0015] In step 1, the molar ratio of tungsten powder, molybdenum powder, boron powder and aluminum powder (or 6061 aluminum alloy powder) is W:Mo:B:Al=(0.6-0.95):(0.05-0.4):(0.8-1.2):(1.0-2.0); the zinc stearate activator is 0.3-1wt.% of the original ingredients.
[0016] In step 2, the ball milling medium is any one of agate balls, silicon nitride balls, stainless steel balls and zirconia balls, the predetermined rotation speed is 100 to 300 r / min, and the predetermined dry mixing time is 6 to 26 hours.
[0017] In step 4, the pre-pressing pressure is 7-15 MPa, and the pressure of the vacuum environment is 3×10 -3 ~5×10 -1 Pa.
[0018] In step 4, the predetermined heating rate is 5 to 20° C. / min, the predetermined sintering temperature is 800 to 980° C., the predetermined pressure is 30 to 60 MPa, and the predetermined heat preservation and pressure holding time is 1 to 15 h.
[0019] In step 4, after the sintering temperature reaches 200-400° C., pressurization is performed at a predetermined pressurization rate of 0.1-2 MPa / min to a predetermined pressure.
[0020] In step 5, the predetermined cooling rate is 100-200° C. / h.
[0021] The preparation method of the present invention uses relatively economical initial materials, can save costs, and the raw materials used are simple, available on the market, and easy to obtain; the obtained (W x Mo 1-x )AlB ceramic bulk material has high phase purity, as well as good mechanical properties, thermal conductivity and thermal stability.
[0022] The present invention provides (W x Mo 1-x )AlB-MAB phase metal ceramic shielding material can be used as a neutron shielding material with integrated function and structure at an ambient temperature of 500-800℃. The shielding material has moderate density, but has strong shielding function for neutrons and gamma rays of various energy bands, high mechanical strength, good thermal stability and corrosion resistance. The present invention is particularly suitable for important occasions such as small and mobile reactors, and shielding materials for radiation medicine. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The present invention (W x Mo 1-x ) Flow chart of the preparation method of AlB-MAB phase metal ceramic shielding material.
[0024] Figure 2 is prepared in Example 1 of the present invention (W x Mo 1-x )X-ray diffraction refinement pattern of AlB-MAB phase metal ceramic shielding material.
[0025] Figure 3 is prepared in Example 4 of the present invention (W x Mo 1-x )Bending stress-strain curve of AlB-MAB phase metal ceramic shielding material.
[0026] Figure 4 is prepared in Example 1 of the present invention (W x Mo 1-x )Scanning electron microscope (SEM) image of AlB-MAB phase metal ceramic shielding material.
[0027] Figure 5 The neutron transmittance of Cf252 source of different materials varies with shielding thickness.
[0028] Figure 6 The Co60-1.25MeV γ-ray transmittance of different materials varies with shielding thickness. DETAILED DESCRIPTION
[0029] The present invention is further described below through specific embodiments. Figure 1 is (W of Embodiments 1 to 6 of the present invention x Mo 1-x ) Flow chart of the preparation method of AlB-MAB phase metal ceramic shielding material.
[0030] Example 1, a high-purity, dense, high-temperature resistant neutron and gamma-ray comprehensive shielding material (W 0.95 Mo 0.05 ) The preparation of AlB ceramic bulk material comprises the following steps:
[0031] Step S1, using raw materials tungsten powder, molybdenum powder, boron powder, and aluminum powder in a molar ratio of W:Mo:B:Al=0.95:0.05:1:1.3, adding 0.7wt.% of stearate zinc activator based on the total mass of the raw materials, and mixing to obtain original ingredients, the total mass of the original ingredients is about 100g.
[0032] Step S2, placing the original ingredients in a stainless steel ball mill, adding stainless steel balls into the stainless steel mill, the ball-to-material ratio is 2:1, the mass ratio of medium balls (d=10 mm): small balls (d=6 mm) is 1:1, and the stainless steel ball mill containing the original ingredients is evacuated before ball milling. After evacuation, dry mixing is performed on a planetary ball mill at 300 r / min for 6 hours to obtain a mixture.
[0033] Step S3, separating the mixed material and the ball milling medium using a sieve with an aperture of 50 mesh (0.28 mm) to obtain a mixed material.
[0034] Step S4, placing the mixture in a graphite mold, placing the graphite mold in a hot press furnace and pre-pressing at 10MPa, then heating at a heating rate of 10°C / min in a vacuum environment (pressure ~3E-1Pa), and after the sintering temperature reaches 300°C, pressurizing at a predetermined pressurizing rate of 0.5MPa / min, and finally sintering at a sintering temperature of 830°C, a pressure of 35MPa, and a heat and pressure holding time of 5 hours. Its X-ray diffraction refinement pattern is shown in Figure 2 , Scanning electron microscope (SEM) image see Figure 3 .
[0035] Step S5, after the heat preservation and pressure preservation are completed, the temperature is lowered to room temperature at a cooling rate of 150°C / h to obtain a dense (W 0.95 Mo 0.05 )AlB ceramic material.
[0036] The (W 0.95 Mo 0.05 )The purity of AlB ceramic material is 96.3wt.%, the density is 87.2%, and the flexural strength is 440MPa.
[0037] Embodiment 2, a kind of high purity dense (W 0.80 Mo 0.20 ) The preparation of AlB ceramic bulk material comprises the following steps:
[0038] Step S1, mixing raw materials tungsten powder, molybdenum powder, boron powder and aluminum powder in a molar ratio of W:Mo:B:Al=0.8:0.2:1:1.3, 62.5g of tungsten powder, 8.2g of molybdenum powder, 4.6g of boron powder, 14.9g of aluminum powder, and 0.7wt.% of zinc stearate activator, the total mass of the original ingredients is about 90g.
[0039] Step S2, placing the original ingredients in a stainless steel ball mill, adding stainless steel balls into the stainless steel ball mill, the ball-to-material ratio is 2:1, the mass ratio of medium balls (d=10 mm): small balls (d=6 mm) is 1:1, the stainless steel ball mill is evacuated before ball milling, and after evacuation, dry-mixing is performed at 200 r / min for 15 hours using a ball mill to obtain a mixture.
[0040] Step S3, separating the mixed material and the ball milling medium using a sieve with an aperture of 50 mesh to obtain a mixed material.
[0041] Step S4, placing the mixture in a graphite mold, placing the graphite mold in a hot press furnace and pre-pressing it at 10 MPa, then heating it in a vacuum environment (pressure <1E-2Pa) at a heating rate of 10°C / min, and after the sintering temperature reaches 300°C, pressurizing it at a predetermined pressurizing rate of 30 MPa / h, and finally sintering it at a sintering temperature of 870°C, a pressure of 40 MPa, and a heat and pressure holding time of 5 hours.
[0042] Step S5, after the heat preservation and pressure preservation are completed, the temperature is lowered to room temperature at a cooling rate of 120°C / h to obtain a dense (W 0.80 Mo 0.20 )AlB ceramic material.
[0043] The (W 0.80 Mo 0.20 )The purity of AlB ceramic material is 94.6wt.%, the density is 92%, and the flexural strength is 376MPa.
[0044] Embodiment 3, a high-purity high-temperature resistant neutron and gamma-ray comprehensive shielding material (W 0.95 Mo 0.05 ) The preparation of 6061AlB ceramic block comprises the following steps:
[0045] Step S1, using raw materials tungsten powder, molybdenum powder, boron powder, and 6061 aluminum alloy powder in a molar ratio of W:Mo:B:6061Al=0.95:0.05:1:1.3, including 74.42g of tungsten powder, 2.04g of molybdenum powder, 4.61g of boron powder, and 15.56g of 6061 aluminum alloy powder, and adding 0.5wt.% of stearate zinc activator based on the total mass of the raw materials to obtain the original ingredients, and the total mass of the original ingredients is about 100g.
[0046] Step S2, placing the original ingredients in a stainless steel ball mill, adding stainless steel balls into the stainless steel mill, the ball-to-material ratio is 2:1, the mass ratio of medium balls (d=10 mm): small balls (d=6 mm) is 1:1, the stainless steel ball mill is evacuated before ball milling, and after evacuation, dry-mixing is performed on a planetary ball mill at 300 r / min for 15 hours to obtain a mixture.
[0047] Step S3, separating the mixed material and the ball milling medium using a sieve with an aperture of 50 mesh to obtain a mixed material.
[0048] Step S4, placing the mixture in a graphite mold, and then heating it in a vacuum environment (pressure <6E-3Pa) at a heating rate of 10°C / min. After the sintering temperature reaches 300°C, pressurizing it at a predetermined pressurizing rate of 0.7MPa / min, and finally sintering it at a sintering temperature of 800°C, a pressure of 35MPa, and heat and pressure maintenance for 5 hours.
[0049] Step S5, after the heat preservation and pressure preservation are completed, the temperature is lowered to room temperature at a cooling rate of 150°C / h to obtain a dense (W 0.95 Mo 0.05 )6061AlB ceramic material.
[0050] The (W 0.95 Mo 0.05 )The purity of 6061AlB ceramic material is 92wt.%, the density is 85.6%, and the flexural strength is 484MPa.
[0051] Embodiment 4, a kind of high purity dense (W 0.80 Mo 0.20 ) The preparation of 6061AlB ceramic bulk material comprises the following steps:
[0052] Step S1, mix the raw materials tungsten powder, molybdenum powder, boron powder and 6061 aluminum alloy powder in a molar ratio of W:Mo:B:Al=0.8:0.2:1:1.3, add 0.7wt.% of stearate zinc activator based on the total mass of the raw materials to obtain the original ingredients, the total mass of the original ingredients is about 90g.
[0053] Step S2, placing the original ingredients in a stainless steel ball mill, adding stainless steel balls into the stainless steel ball mill, the ball-to-material ratio is 2:1, the mass ratio of medium balls (d=10 mm): small balls (d=6 mm) is 1:1, the stainless steel ball mill is evacuated before ball milling, and after evacuation, dry-mixing is performed on a ball mill at 300 r / min for 15 hours to obtain a mixture.
[0054] Step S3, separating the mixed material and the ball milling medium using a sieve with an aperture of 50 mesh to obtain a mixed material.
[0055] Step S4, placing the mixture in a graphite mold, placing the graphite mold in a hot press furnace and pre-pressing it at 10 MPa, then heating it in a vacuum environment (pressure <5E-3Pa) at a heating rate of 10°C / min, and after the sintering temperature reaches 300°C, pressurizing it at a predetermined pressurizing rate of 0.4 MPa / min, and finally sintering it under the parameter conditions of a sintering temperature of 920°C, a pressure of 35 MPa, and a heat and pressure holding time of 5 hours.
[0056] Step S5, after the heat preservation and pressure preservation are completed, the temperature is lowered to room temperature at a cooling rate of 150°C / h to obtain a dense (W 0.80 Mo 0.20 )AlB ceramic material. Its bending stress-strain curve is shown in Figure 4 .
[0057] The (W 0.80 Mo 0.20 )The purity of 6061AlB ceramic material is 94.0wt.%, the density is 96%, and the flexural strength is 600MPa.
[0058] Example 5, a high-purity, dense, high-temperature resistant neutron and gamma-ray comprehensive shielding material (W 0.95 Mo 0.05 )Al 1.8 The preparation of B ceramic block material comprises the following steps:
[0059] Step S1, using raw materials of tungsten powder, molybdenum powder, boron powder and aluminum powder in a molar ratio of W:Mo:B:Al=0.95:0.05:1:1.8, adding 0.7wt.% of stearate zinc activator based on the total mass of the raw materials, and mixing to obtain the original ingredients.
[0060] Step S2, placing the original ingredients in a stainless steel ball mill, adding stainless steel balls into the stainless steel mill, the ball-to-material ratio is 2:1, the mass ratio of medium balls (d=10 mm): small balls (d=6 mm) is 1:1, the stainless steel ball mill is evacuated before ball milling, and after evacuation, dry mixing is performed on a ball mill at 300 r / min for 15 hours.
[0061] Step S3, separating the mixed material and the ball milling medium using a 50-mesh screen to obtain a mixed material.
[0062] Step S4, placing the mixture in a graphite mold, placing the graphite mold in a hot press furnace and pre-pressing it at 10MPa, then heating it in a vacuum environment (pressure <3E-3Pa) at a heating rate of 10°C / min, and after the sintering temperature reaches 300°C, pressurizing it at a predetermined pressurizing rate of 0.5MPa / min, and finally sintering it at a sintering temperature of 800°C, a pressure of 35MPa, and heat and pressure maintenance for 5 hours.
[0063] Step S5, after the heat preservation and pressure preservation are completed, the temperature is lowered to room temperature at a cooling rate of 150°C / h to obtain a dense (W 0.95 Mo 0.05 )6061Al 1.8 B. Ceramic materials.
[0064] The (W 0.95 Mo 0.05 )Al 1.8 The purity of B ceramic material is 92.7wt.%, the density is 86.6%, and the flexural strength is 386MPa.
[0065] According to the high-purity dense (W x Mo 1-x )AlB ceramic block material preparation method, using tungsten powder, molybdenum powder, boron powder, aluminum powder (or 6061 aluminum alloy powder) as raw materials, and adding zinc stearate as an active agent to prepare ingredients to obtain original ingredients; then adding ball milling media to the original ingredients, and dry mixing them on a ball mill for a predetermined time to obtain a mixture; then sieving the mixture with a screen; then pre-pressing the mixture, and then heating and pressurizing the mixture in a vacuum environment or a protective atmosphere at a predetermined heating rate and a predetermined pressurizing rate, and after reaching a predetermined sintering temperature and a predetermined pressure, sintering is performed at a predetermined heat preservation and pressure holding time to obtain a sintered block; finally, cooling the sintered block to room temperature at a predetermined cooling rate to obtain a high-purity and dense (W x Mo 1-x )AlB ceramic block material. The initial materials used in the above process are relatively economical and cost-saving, and the raw materials used are simple, available on the market, easy to obtain and cheap, which facilitates the implementation of the process.
[0066] In addition, Examples 1 to 5 of the present invention creatively synthesized dense (W x Mo 1-x )AlB bulk material, the obtained (W x Mo 1-x)AlB ceramic block material purity is as high as 92-96wt.%, density is up to 85-96%, bending strength is 370-600MPa. x Mo 1-x ) The shielding effect of AlB ceramic bulk materials on neutrons and gamma rays is first theoretically 0.95 Mo 0.05 AlB and W 0.8 Mo 0.2 The AlB material was compared with some typical shielding materials, and their neutron and gamma-ray transmittances were calculated using a Monte Carlo program (MCNP5). Figure 5 , 6 Then, the sintered sample was subjected to 252Cf neutron source and 60 Co-1.25MeV gamma ray shielding performance test. For samples 3 and 4, when W 0.95 Mo 0.05 AlB at a thickness of 33 mm and W 0.8 Mo 0.2 AlB at a thickness of 29 mm 252 The transmittance of Cf neutron source is 45.6% and 49.6% respectively, and the shielding effect is 54.4% and 50.4% respectively, which is 1.4 and 1.28 times lower than that of the typical neutron / γ-ray shielding material boron steel. 60 Co-1.25MeV γ-ray transmittance, W 0.95 Mo 0.05 AlB and W 0.8 Mo 0.2 The linear attenuation coefficients of AlB are 0.606 cm -1 and 0.513cm -1 , while boron steel is 0.39cm -1 It can be proved that the (WxMo1-x)AlB ceramic bulk material prepared by the present invention has a good shielding effect on neutrons and gamma rays, and has a certain structural strength, and can be widely used as a functional / structural integrated shielding material in small and mobile reactors, radiation medicine and other fields.
Claims
1. A metal ceramic shielding material for shielding neutrons and gamma rays, characterized in that: W x Mo 1-x )AlB-MAB solid solution phase compound has a monoclinic cubic crystal structure, a space group of Cmcm, and a unit cell composed of alternating stacking of MB units and A atomic planes; the compound is composed of elements W, Mo, Al or 6061Al alloy and B, Mo is the solid solution atom of W at the M position, the atomic concentration x of Mo is 5-40at%, and the alloying elements Si and Mg atoms in the 6061Al alloy are mainly at the A position.
2. The metal ceramic shielding material for shielding neutrons and gamma rays according to claim 1, characterized in that: The molar ratio of the elements tungsten, molybdenum, boron, aluminum or 6061 aluminum alloy is W:Mo:B:Al=(0.6-0.95):(0.05-0.4):(0.8-1.2):(1.0-2.0).
3. A method for preparing the metal ceramic shielding material as claimed in claim 1, characterized in that: The specific steps are: Step 1, preparing boron powder, tungsten powder, molybdenum powder and aluminum powder or 6061Al alloy powder as raw materials to obtain original ingredients; Step 2, adding ball milling media to the original ingredients, and performing ball milling and dry mixing on a ball mill; Step 3, separating the mixed material and the ball milling medium with a sieve to obtain a mixed material; Step 4, pre-pressing the dried mixed material, and then heating and pressurizing the mixed material in a vacuum environment or a protective atmosphere at a predetermined heating rate and a predetermined pressurizing rate, and after reaching a predetermined sintering temperature and a predetermined pressure, sintering the mixed material at a predetermined heat preservation and pressure preservation time to obtain a sintered block; Step 5, cooling the sintered block to room temperature to obtain high-purity and dense (W x Mo 1-x )AlB-MAB phase ceramic bulk material.
4. The preparation method according to claim 3, characterized in that: In step 1, the molar ratio of tungsten powder, molybdenum powder, boron powder, aluminum powder or 6061 aluminum alloy powder is: W:Mo:B:Al=(0.6-0.95):(0.05-0.4):(0.8-1.2):(1.0-2.0).
5. The preparation method according to claim 4, characterized in that: In step 2, the ball milling medium is any one of agate balls, silicon nitride balls, stainless steel balls and zirconia balls, the ball milling speed is 100 to 300 r / min, and the ball milling dry mixing time is 6 to 26 hours.
6. The preparation method according to claim 5, characterized in that: In step 4: The pre-pressing pressure is 7-15 MPa, and the vacuum pressure is 3×10 -3 ~5×10 -1 Pa; The predetermined heating rate is 5-20°C / min, the predetermined sintering temperature is 800-980°C, the predetermined pressure is 30-60MPa, and the predetermined heat preservation and pressure holding time is 1-15h; Wherein, after the sintering temperature reaches 200-400° C., pressurization is performed at a pressurization rate of 0.1-2 MPa / min to a predetermined pressure.
7. The preparation method according to claim 6, characterized in that: In step 5, the cooling rate is 200-250°C / h.
Citation Information
Patent Citations
Preparation method of high-purity MoAlB ceramic powder and compact block body
CN107512912A
High-purity compact WAlB MAB phase ceramic block material and preparation method thereof
CN114276146A
Ceramic material for shielding gamma and neutron rays and preparation method thereof
CN117660822A
Gd-doped MoAlB structure and function integrated shielding material and preparation method thereof
CN118241096A
Bimodal and multimodal dense boride cermets with superior erosion performance
US20070128066A1